ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PROCUREMENT FRAUD PADA LINGKUNGAN INSTANSI PEMERINTAHAH (Studi Kasus Pada SKPD Kabupaten Bireuen) - Nurmalia Nurmalia; Hendra Raza; Muhammad Haykal; Yunina Yunina (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Malikussaleh, 2025)
This study aims to analyze the factors influencing procurement fraud within government institutions, focusing on a case study of SKPD in Bireuen District. Procurement fraud refers to illegal actions carried out during the procurement process, often resulting in financial losses and undermining the integrity of public services. The study examines three key factors: the quality of the procurement committee, risk assessment in procurement, and the procurement environment, to determine their impact on the occurrence of procurement fraud. Data was collected from 98 respondents working in SKPD through a structured questionnaire. The analysis was conducted using multiple linear regression. The results show that risk assessment has a significant impact on procurement fraud, while the quality of the procurement committee and the procurement environment do not have significant effects..